Targeting Discoidin Domain Receptors DDR1 and DDR2 overcomes matrix‐mediated tumor cell adaptation and tolerance to BRAF‐targeted therapy in melanoma. Issue 2 (27th December 2021) - Berestjuk, Ilona; Lecacheur, Margaux; Carminati, Alexandrine; Diazzi, Serena; Rovera, Christopher; Prod'homme, Virginie; Ohanna, Mickael; Popovic, Ana; Mallavialle, Aude; Larbret, Frédéric; Pisano, Sabrina; Audebert, Stéphane; et al.
Abstract: Resistance to BRAF/MEK inhibitor therapy in BRAF V600 ‐mutated advanced melanoma remains a major obstacle that limits patient benefit. Microenvironment components including the extracellular matrix (ECM) can support tumor cell adaptation and tolerance to targeted therapy; however, the underlying mechanisms remain poorly understood. Here, we investigated the process of matrix‐mediated drug resistance (MMDR) in response to BRAF V600 pathway inhibition in melanoma. We demonstrate that physical and structural cues from fibroblast‐derived ECM abrogate anti‐proliferative responses to BRAF/MEK inhibition. MMDR is mediated by drug‐induced linear clustering of phosphorylated DDR1 and DDR2, two tyrosine kinase collagen receptors. Depletion and pharmacological targeting of DDR1 and DDR2 overcome ECM‐mediated resistance to BRAF‐targeted therapy. In xenografts, targeting DDR with imatinib enhances BRAF inhibitor efficacy, counteracts drug‐induced collagen remodeling, and delays tumor relapse. Mechanistically, DDR‐dependent MMDR fosters a targetable pro‐survival NIK/IKKα/NF‐κB2 pathway. These findings reveal a novel role for a collagen‐rich matrix and DDR in tumor cell adaptation and resistance. They also provide important insights into environment‐mediated drug resistance and a preclinical rationale for targeting DDR signaling in combination with targeted therapy in melanoma. Synopsis: Resistance to MAPK targeted therapy remains a major challenge in melanoma management. This study shows that BRAF/MEK inhibitor combination induces collagen remodeling that fosters activation of Discoidin Domain Receptors (DDR) and turns on a drug tolerant pathway. Targeting DDR overcomes this pathway. Adhesion of BRAF‐mutated melanoma cells to extracellular matrix generated from melanoma associated fibroblasts (MAF) confers tolerance to BRAF and MEK inhibition. Collagen receptors DDR promote tumor cell survival and matrix‐mediated drug resistance (MMDR) to combined MAPK targeted agents through NIK and non‐canonical NFκB2 signaling. DDR inhibition increases response to oncogenic BRAF inhibition, suppresses therapy‐induced collagen remodeling and induces tumor cell death in melanoma xenografts. Triple‐drug combination using BRAF/MEK inhibitors and DDR inhibitor such as imatinib, a clinically approved drug for leukemia, is proposed as a novel therapeutic strategy against disease relapse. Abstract : Resistance to MAPK targeted therapy remains a major challenge in melanoma management. This study shows that BRAF/MEK inhibitor combination induces collagen remodeling that fosters activation of Discoidin Domain Receptors (DDR) and turns on a drug tolerant pathway. Targeting DDR overcomes this pathway.